An assessment of relations between smart growth and social cohesion in regional dimension - Bal-Domańska, Beata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
The objective of the study is to provide an assessment of relations combining smart growth and social cohesion, as well as to identify how and which social cohesion dimensions are involved in the relationships with smart growth. The analysis covered the period 2003-2013. Smart growth was described by using three pillars: smart specialization, creativity and innovation, whereas social cohesion was defined from the perspective of the most important problems grouped in five categories: income, young people in the labour market, unemployment, gender equality and demography. Panel (LSDV) and cross-section models were used for the assessment of relations between smart growth and social cohesion. LSDV models allow for including in the model, specific for a given region, the factors derived from location, resources, economic, cultural and political determinants, as well as other aspects which are unobservable and not included in the model. One-year models allow for identifying cross-section relations. The obtained results emphasize the significance of growth factors, related to human capital, for social cohesion. Regional creativity, manifested by the skills and education of the workforce presented the highest consistency with social cohesion improvement (especially in terms of unemployment – including youth unemployment – and income categories). The relations with smart specialization, defined as human resources and human capital in high and medium high-technology manufacturing and knowledge-intensive services, were also recognized as significant. The least significant relationships were identified for regional innovation, estimated based on expenditure on research and development in the business sector
Argumenta Oeconomica, 2018, Nr 1 (40), s. 21-52
Keywords: social cohesion; smart growth; EU regions